Effect of different endotracheal suctioning methods on clearance of airway secretions in patients with craniocerebral injury and tracheotomy (不同吸痰方式对颅脑损伤气管切开患者气道分泌物清除的效果观察) - AN Delian (安德连); DAI Meng (戴萌); WEI Xiaomei (卫小梅); TANG Zhiming (唐志明); XU Ziyang (许自阳); WEN Hongmei (温红梅); DOU Zulin (窦祖林) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of endotracheal suctioning method using suctioning sputum with suctioning salivary tube in patients with craniocerebral injury undergoing tracheotomy. Methods A randomized controlled trial was conducted in 106 patients with traumatic brain injury after tracheotomy who met the inclusion criteria. According to the random number table method, they were divided into two groups, with 53 cases in each group. The experimental group was treated with endotracheal suctioning method using sputum suction tube combined with sputum suction tube, while the control group was treated with routine sputum suction method using sputum suction tube . The secretion severity grade under electronic laryngoscope swallowing function assessment (FEES) before and after sputum aspiration was compared between the two groups. The number of sputum aspiration, blood oxygen saturation and heart rate changes at 1 minute before and after sputum aspiration were observed in the two groups at 1, 3 and 7 days after admission. The mucosal damage under electronic hose bronchoscopy was observed in the two groups at 1, 3 and 7 days after admission. Results The severity of FEES was significantly lower in the experimental group than in the control group (P<0. 05). There was no significant difference in blood oxygen saturation between the experimental group and the control group one minute before sputum aspiration (P＞0. 05). The blood oxygen saturation after sputum aspiration was higher than that of the control group, and the difference was statistically significant (P<0. 05). There was no significant difference in heart rate between the experimental group and the control group 1 minute before sputum aspiration (P＞0. 05). The heart rate one minute after sputum aspiration was lower than that of the control group, and the difference was statistically significant (P<0. 05). The number of sputum aspiration in the experimental group was lower than that in the control group, and the difference was statistically significant(P<0. 05). The total incidence of mucosal damage was lower than that of the control group, and the difference was statistically significant (P<0. 05). Conclusion Sputum suction combined with sputum suction tube has significant curative effect, alleviates the pain of patients, and has fewer complications, significantly reduces the incidence of airway mucosal injury, and has high safety. (目的 探讨吸唾管结合吸痰管吸痰法在颅脑损伤气管切开患者中的应用效果。方法 采用随机对照试验研究方法, 对符合纳入标准的106例颅脑损伤气管切开后住院患者, 根据随机数字表法分为两组, 每组 53例。对照组采用吸痰管常规吸痰法进行治疗和护理, 试验组采用吸唾管结合吸痰管吸痰法进行治疗和护理。比较两组患者吸痰前后的电子喉镜吞咽功能评估(FEES)下分泌物严重程度分级; 两组患者入院后第1、3、7天的吸痰次数、吸痰前后1 min血氧饱和度及心率变化情况, 观察两组住院患者第1、3、7天电子软管支气管镜下黏膜破损情况。结果 试验组吸痰后电子喉镜吞咽功能评估(FEES)分泌物严重程度分级低于对照组, 差异具有统计学意义(P<0. 05)。试验组吸痰前1 min的血氧饱和度与对照组比较, 差异无统计学意义(P＞0. 05); 吸痰后的血氧饱和度高于对照组, 差异有统计学意义(P<0. 05)。试验组吸痰前1 min的心率与对照组比较, 差异无统计学意义(P＞0. 05); 吸痰后1 min的心率低于对照组, 差异有统计学意义(P<0. 05)。试验组吸痰次数低于对照组, 差异有统计学意义(P<0. 05)。黏膜破损总发生率低于对照组, 差异有统计学意义(P<0. 05)。结论 吸唾管结合吸痰管吸痰法的气道分泌物清除效果明确, 减轻患者痛苦, 且并发症较少, 显著降低了气道黏膜损伤的发生率, 安全性较高。)